FRI0446 Prevalence and characteristics of spondyloarthritis according to asas criteria in patients with inflammatory bowel disease – results from the spice cohort. (15th June 2017) - Haschka, J; Hirschmann, S; Kleyer, A; Englbrecht, M; Zimmermann, J; Faustini, F; Simon, D; Figueiredo, CP; Cavallaro, A; Muschitz, C; Kocijan, R; Resch, H; et al.
Abstract : Background: Musculoskeletal symptoms are considered as one of the most frequent extra-intestinal manifestation in Inflammatory Bowel Disease (IBD) patients with a prevalence of up to 40% involving axial and/or peripheral joints. Data on the prevalence of musculoskeletal disease, in particular of SpA are limited and vary considerably due to different criteria the studies have used to define musculoskeletal disease in IBD patients. Objectives: To define the prevalence of axial and peripheral spondyloarthritis (SpA) according to Assessment of Spondyloarthritis International Society (ASAS) in patients with Crohn's disease (CD) and ulcerative colitis (UC). Methods: The SPICE cohort (Spondyloarthritis in Inflammatory Bowel Disease Cohort Erlangen) comprises prospectively recruited colonoscopy- proven Crohn's Disease (CD) or Ulcerative Colitis (UC) patients, who received a pre-defined and standardized musculoskeletal assessment by the rheumatologist. Duration and activity of gastrointestinal and rheumatic disease (axial and peripheral) was documented and fulfillment of ASAS classification criteria for axial and peripheral SpA was tested. Results: 102 IBD patients (62 with CD and 40 with UC) with a median (IQR) disease of 11.0 (18.0) years were assessed. 38.2% fulfilled ASAS criteria for SpA with no difference between CD and UC. ASAS axial SpA criteria were fulfilled by 12%, ASAS peripheral SpA criteria by 31.4% of the IBD patients. Inflammatory back pain was present in 24.5% with MRI signs of sacroiliitis in 48% of IBD patients with inflammatory back pain. Disease activity according to ASDAS-CRP was moderate to high in 91% of the patients with axial SpA. Peripheral arthralgia was present in 71.6%, while arthritis was found in 18.6% of the IBD patients. Conclusions: Both major forms of IBD show a similar burden of musculoskeletal disease. More than one third of inflammatory bowel disease patients show axial or peripheral SpA according to ASAS criteria. Peripheral SpA is more commonly found than axial SpA. References: Harbord M, Annese V, Vavricka SR, et al. The first European evidence-based consensus on extra-intestinal manifestations in inflammatory bowel disease. J Crohn Colitis 2016; 239–254. Karreman MC, Luime JJ, Hazes JMW, Weel AEAM. The prevalence and incidence of axial and peripheral spondyloarthritis in inflammatory bowel disease: a systematic literature review and meta-analysis. J Crohn Colitis 2016; 1–12. Disclosure of Interest: None declared